ASSOCIATION BETWEEN ARTERIAL PRESSURE, BMI AND SOME CHANGEABLE BIOCHEMISTS IN PUBLIC SERVERS OF THE FEDERAL UNIVERSITY OF PARANÁ - UFPR (Fiep Bulletin - online, 2014)
The aim of the present study was to verify and to correlate changeable  that correspond with the health level  in a public servers of the Federal University of Paraná - UFPR (44,81± years old; 67,03± 12,76 kg; 160 ± 0,7 cm). The sample was composed for 313 women. The body mass index was verified (IBMI); glicemy (GL), triglycerides (TR) and total cholesterol (CT) by capillary blood samples; systolic blood pressure (SBP) and diastolic blood pressure (DBP). For the statistical treatment program SPSS 13,0 was used. The test of normality of Shapiro-Wilk was applied. Descriptive statistics was used and the coefficient of simple correlation of Pearson (p
Keywords: Arterial pressure; BMI; biochemists variable